1989
DOI: 10.1021/jm00131a003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of methotrexate-antibody conjugates by regiospecific coupling and assessment of drug and antitumor activities

Abstract: In order to increase the retention of drug activity, regiospecific coupling has been used to synthesize conjugates of methotrexate (MTX, 1) with normal rabbit IgG (NRG) and a mouse anti-human renal cancer monoclonal IgG (Dal K-20). MTX gamma-methyl ester (4) was produced either by selective esterification of MTX or by coupling of 4-amino-4-deoxy-N10-methylpteroic acid (2) with suitable glutamic acid derivatives. The MTX gamma-methyl ester (4) was then converted to the corresponding hydrazide 6. An amide-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…This compound is a potent inhibitor of the enzyme dihydrofolate reductase, which is responsible for recycling 7,8-dihydrofolate to its reduced, physiologically active 6(R)-tetrahydro form (5). Although not all types of tumors are affected by MTX, this cytotoxic agent has been used successfully in chemotherapy for more than 4 decades.…”
mentioning
confidence: 99%
“…This compound is a potent inhibitor of the enzyme dihydrofolate reductase, which is responsible for recycling 7,8-dihydrofolate to its reduced, physiologically active 6(R)-tetrahydro form (5). Although not all types of tumors are affected by MTX, this cytotoxic agent has been used successfully in chemotherapy for more than 4 decades.…”
mentioning
confidence: 99%
“…MTX has been coupled to antibody amino groups and carbohydrates either directly or through various intermediate carriers (reviewed [11]; for more recent discussion, see [1,17,18,25,31,32,36,37]). Release of free drug from immunoconjugates has been a persistent problem.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, conjugation to IgG antibodies gave enhanced specificity, but resulted in lowered drug efficacy and antibody binding [5,7,10,11,15,19,20,24,29]. More recently, several groups have made improved methotrexate conjugates having an efficacy greater than the equimolar drug and little loss of antibody binding capacity [17,18,23,30,31,32,36].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that enhanced antibody affinity leads to increased endocytosis of the immunoconjugate and potentiation of cytotoxicity. KRALOvEC et al (1989) used a regiospecific coupling method to bind MTX to a mouse anti-human renal cancer monoclonal IgG . Two conjugates were synthesized.…”
Section: A) Antibody Binding Methodsmentioning
confidence: 99%